Autism Spectrum Disorder and Early Psychosis: a narrative review from a neurodevelopmental perspective - Guerrera, Silvia; Pontillo, Maria; Chieppa, Fabrizia; Passarini, Sara; Di Vincenzo, Cristina; Casula, Laura; Di Luzio, Michelangelo; Valeri, Giovanni; Vicari, Stefano (Frontiers in Psychiatry, 2024)
Autism Spectrum Disorder (ASD), characterized by socio-communicative abnormalities and restricted, repetitive, and stereotyped behaviors, is part of Neurodevelopmental Disorders (NDDs), a diagnostic category distinctly in accordance with the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition, (DSM-5), clearly separated from Schizophrenia Spectrum Disorder (SSD) (schizophrenia, schizophreniform disorder, schizoaffective disorder, schizotypal personality disorder). Over the last four decades, this clear distinction is gradually being replaced, describing ASD and SSD as two heterogeneous conditions but with neurodevelopmental origins and overlaps. Referring to the proposal of a neurodevelopmental continuum model, the current research's aim is to provide an update of the knowledge to date on the course of clinical symptoms and their overlaps among ASD and SSD. A narrative review of the literature published between January 2010 and June 2023 was conducted. Five studies were included. All studies show a global impairment in both conditions. Two studies show a focus on neurodevelopmental perspective in ASD and SSD. Only one study of these adopts a longitudinal prospective in terms of prognostic markers among ASD and SSD. Three Some studies underline the overlap between ASD and SSD in terms of negative, disorganized and positive symptomatology on the social-reciprocity domain impairments. Two studies show a pattern of association regarding the disorganized symptomatology. Only one study of these adopts a longitudinal prospective in terms of prognostic markers among ASD and SSD. To date, there is a gap in the current scientific literature focused on ASD-SSD course of clinical symptoms and their overlaps from a Codice campo modificato neurodevelopmental perspective. Future longitudinal studies to identify risk markers and tailored treatments are needed.